Evolutionary biology (Appleton, 1969)
This book introduction cancer cells as temperature sensitive mutants, origin of mammals, comparative ecogentics of two avena species occurring in central california, some aspects of the evolution of social bess, sexual selection in drosophila, defenses against visually hunting predatoes, evolution in parthenogenetic curculionidae.